Therapeutic Potential of Silicon Supplementation in Age-Related Diseases: A Comprehensive Review - Koczkodaj, Maria; Kotowicz, Michał; Mormul, Agata (Quality in Sport, 2024)
Silicon, the second most abundant element in nature, plays a crucial role in human health. Despite its understated presence, silicon’s multifaceted contributions to various physiological processes make it a promising option for therapeutic intervention. Through a comprehensive analysis of recent scientific literature, this review explores the impact of silicon supplementation on bone health, cardiovascular function, metabolic regulation, and neuroprotection. Review methods involved the analysis of scientific publications found in databases such as PubMed and scientific journals, including meta-analyses, randomized trials, and systematic reviews, concerning the scope of medical and nutritional problems, excluding case reports. Key findings suggest that silicon supplementation may positively influence bone mineral density, bone regeneration, and collagen synthesis, offering potential benefits for individuals at risk of osteoporosis and musculoskeletal disorders. Furthermore, evidence highlights silicon’s role in regulating cardiovascular health, indicating its potential to mitigate atherosclerosis risk and improve lipid profiles, thereby offering promise in managing conditions such as diabetes and dyslipidemia. Additionally, emerging research underscores silicon’s neuroprotective properties, hinting at its potential in combating neurodegenerative diseases like Alzheimer’s. This review emphasizes the promising prospect of silicon supplementation as a complementary strategy for enhancing overall health and addressing age-related diseases.